Comparative analysis of the socio-economic developments and competitiveness of the agri-food sector at a sectoral and macro level in the preaccession countries - Aramyan, Lusine,Galen, Michiel van,Logatcheva, Katja,Herceglic, Nera,Janeska Stamenkovska, Ivana,Koç, Ahmet Ali,Kovacevic, Vlado,Markovic, Milan,Martinovska Stojceska, Aleksandra,Zhllima, Edvin (Publications Office of the European Union, 2022)
This study is a part of a project
10.2762/357839
Keywords: Graue Literatur; agri-foodstuffs; competitiveness; social development; agro-industry; foodstuff; food consumption; economic development; accession to the European Union; comparative analysis; macroeconomics; economic indicator; agricultural production; report